英國學科領導人標準的分析：脈絡課程的觀點An Analysis on the Standard for Subject Leaders: The Viewpoints of Curriculum in Context - 蔡宗河Tsung-Ho Tsai (Higher Education Foundation, 2007)
本文主要是從較傾向公平、正義的《脈絡課程》觀點來分析較傾向績效、卓越的《學科領導人標準》。雖然本文從分析中對這種標準提出許多批評，然而本文認為教育政策的制定往往是反映當時的社會思潮及價值觀，因此，強調績效及卓越的《學科領導人標準》，對我國近年來逐漸朝向標準化的教育政策有其正面的助益及價值，只要在實施的過程中兼顧以下四點，是可以規避其可能的缺失，並創造出最大的效益。首先，如何在重視標準化的政策中，顧及弱勢學校及學生的學習，以避免造成社會對立，促進社會流動，實現社會公平正義。其次，在實施標準化政策時，更應落實教育的多元發展，並推動教育的全人發展；復次，教師如何從教學的過程中誘發學生學習的興趣，恐怕比短期的學習成效來得有價值；最後，在實施標準的過程中更應重視個別學生的成長及學習進步程度，以創造更公平教育。 This article is mainly from the viewpoints of"Curriculum in Context＂that are in favor of fairness and justice to analyze the"Standards for Subject Leaders＂(SfSL) whose viewpoints relatively advocate achievement and excellence. By way of this analysis, this article proposes a lot of criticism of SfSL, but it also pinpoints that the formulation of the educational policy is often to reflect the social ideological trend and values at that time. The author still gives positive credits to the benefits and values of SfSL imposed on the standardization of our educational policy in recent years. As long as the following four aspects taken into consideration, we can avoid its possible side effects and create its greatest substantial effect. Firstly, we should take into account the weak schools and poor students, while paying more attention to the standardized policy, in order to avoid the antagonism of a society, to promote the harmonious flow of a society, and to realize the fairness and justice of a society. Secondly, while enforcing the standardized policy, we should place more emphasis on the fulfillment of our educational multi-respected development, and push for the development of a holistic education. Thirdly, how to bring out the students' interest in learning is more crucial how to ensure the short-termed learning effect of students. Fourthly, we should stress more the extent of individual student's growth and progress in order to create a fairer education.